Rebounding from the brink of extinction: Commercial production of milk amongst pastoralists for climate change resilience in Uganda - Niemi, Ernie; Manyindo, Jacob (Technical Centre for Agricultural and Rural Cooperation, 2018)
Changes in climate that intensify drought and accelerate the spread of livestock parasites and diseases darken the economic future for sub-Saharan pastoralists. Already stressed, as industrial and urban development narrow their access to pastures and water for their animals, many pastoralists face a bleak choice: abandon their livestock and their cultural heritage or die. In Uganda, however, the outlook for pastoralists is becoming much brighter. Thousands of pastoralists in Uganda point the way toward a better option: commercial milk production.